The myth of the democratic project in Zimbabwe: power and politics in the movement for democratic change [1999-2014] - Njodzi, Tinashe (Midlands State University, 2018)
The history of the MDC has been authored by various scholars. Most available literature focused on the emergence of the MDC’s activism in general and was silent on the democratic nature of the party in particular. The role played by public and critical public intellectuals in authoring history about the MDC has been associated with subjectivity vis-à-vis objectivity. Praise texts have been published from a pro-MDC perspective but the nature of democracy in the party has been undermined. The role played by the party in their quest to democratize the Zimbabwean political space was narrated in general and no justice was given on the democratic nature of the MDC. The state has been demonized and seen as contrary to the democratization process in Zimbabwe while the MDC has been viewed as a true icon of democracy. Therefore the study seeks to unearth the falsehoods which have been authenticated in the history of the MDC. It is an attempt by the researcher to relay on the democratic nature of the MDC. The researcher highlights on the diverse reasons behind the party’s first and second split. The research also attempts to unearth the democratic loopholes in the MDC since formation, up until the end of the Government of National Unity. In a bid to make the study objective the study consulted various methodologies inclusive of qualitative and quantitative analysis. Primary and secondary sources were consulted as well. All in all, the study’s main focus is to highlight on the myth of the democratic project in Zimbabwe, closely giving a critical analysis of power and politics in the MDC.